Meaningful programming learning: A Student-Centered Technology Integration Model: Pembelajaran pengaturcaraan bermakna: Model Integrasi Teknologi Berpusatkan Pelajar - Mohamad Judi, Hairulliza; Husin, Nurul Faeizah; Hanawi, Siti Aishah (Jurnal Pendidikan Bitara UPSI, 2022)
Learning in computer programming involves the development of skills by understanding and applying the basic concepts of programming, designing algorithms, writing programs, understanding the syntax and logic of programs. The implementation of technology integration in programming courses has the potential to enhance the teaching and learning process in various ways. Technology integration does not only exposes students to technological developments to support learning materials, but also prepares students to work in the 21st century as well as engages their lives with tools that aid the effectiveness and effectiveness of performing tasks. This paper discusses a student-centered technology integration model that serves as a guide in the implementation of technology integration in meaningful programming learning at the tertiary level. This paper reviews learning models and related theories that underlie the implementation of technology integration in teaching and learning process. Just as learning theories provide a conceptual framework for explaining learning patterns that help find solutions to learning problems, theories in technology integration also aim to guide users to clarify important environments in their implementation. The discussion of the student-centered technology integration model aims to guide researchers to analyse student-centered learning problems in depth and devise strategies for the implementation of effective technology integration.